Fourth Annual Summer Conference at Camp Sierra - Sanford, Louis C.; Missionary District of San Joaquin
Folded brochure advertising Summer Conference of the Episcopal Church San Joaquin Diocese, held at Camp Sierra near Huntington Lake, June 18-23, 1934.